The Correlation Between Students’ Self-Confidence And Their Fluency In Speaking At Eleventh Graders Of SMAN 01 Jereweh Academic Year 2020/2021 - S, K. Dedy Sandiarsa; Suhaili, Muhamad (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
This research aimed to find out the correlation between students’ self-confidence and their fluency in speaking at eleventh graders students of SMAN 01 Jereweh and to find out what is the correlation between students’ self-confidence and their fluency in speaking at Eleventh graders’ of SMAN 01 Jereweh. This research was correlation research is to clarify our understanding of important phenomena by identifying relationship among variables. There are two variables in this research, the independent variable is students’ self-confidence and the dependent variable is fluency in speaking. The sample of this research was XI IPA of SMAN 01 Jereweh. The students consist of 24 students. They were chosen by random sampling. The instrument was used subjective test. The scores were analyzing by use likert scale for fluency and questionnaire. Based on the analysis of data above, it was found 0.999 for the correlation between students’ self-confidence and their fluency in speaking at eleventh graders of SMAN 01 Jereweh is higher than pearson product moment number 22 proportion in one tail 0.3438. The total calculation of correlation is very high. Based on the explanation above, there were correlation between students’ self-confidence and their fluency in speaking at eleventh graders of SMAN 01 Jereweh.